5-Nitroisatin-derived thiosemicarbazones: potential antileishmanial agents. (October 2014) - Pervez, Humayun; Manzoor, Nazia; Yaqub, Muhammad; Khan, Khalid Mohammed
Abstract A series of 29 previously reported N4-substituted 5-nitroisatin-3-thiosemicarbazones 2–30 has been screened for leishmanicidal potential. Compounds 2–4, 7, 8, 10–13, 15–19, 21, 23, 24, 26, 28 and 30 exhibited good to excellent antileishmanial activities with IC50 values ranging from 0.44 ± 0.02 to 32.38 ± 0.66 µg/mL. Of these, 5, 7, 19 and 28 proved to be the most active antileishmanial agents, displaying activities with IC50 values 1.78 ± 0.35, 0.44 ± 0.02, 1.91 ± 0.04 and 4.28 ± 0.75 µg/mL, respectively, which were even better than the standard drug, pentamidine (IC50 = 5.09 ± 0.04 µg/mL). This study presents the first example of exhibition of leishmanicidal potential by isatin-thiosemicarbazones and as such furnishes a solid basis for further research on these compounds to develop more potent antileishmanial agents.